Evaluasi Kurikulum - Vina Putri Rahayu; Hery Noer Aly (Departement of Mathematics Education, 2023)
This study aims to provide information regarding curriculum evaluation. The type of research used is library research. The results of the study show that curriculum evaluation plays an important role both in determining educational policies in general. as well as in decision making in the curriculum. Curriculum evaluation is the application of scientific procedures to collect valid and reliable data to make decisions about the current or implemented curriculum. The evaluation function is to improve a curriculum by providing assistance and giving an award. Several models in curriculum evaluation. namely: the provus discrepancy model, the contingency-congruence model, the CIPP model, the Kemmis Surrogate Experience model, the class action set model and the stake case study model. The instruments used in curriculum evaluation are in the form of tar and non-tests..